Some real Life Application of Derivatives in Economics - Sah, Sarswati Kumari; Sahani, Suresh Kumar; Sahani, Kameshwar; Sharma, Dhiraj Kumar (Mikailalsys Journal of Advanced Engineering International, 2024)
In this assignment, we addressed the usage of derivatives in several areas of economics, such as demand elasticity, cost minimization, and profit maximization. In addition, derivatives are used to calculate marginal revenue, marginal cost, and marginal product. This work is motivated by the work of [1-24].